Fluorescent sensor material for detecting metal ions in seawater, preparation method and application thereof
The fluorescent sensor material formed by complexing 2,2'-bipyridine and laminarin with trivalent terbium ions solves the problems of easy aggregation and toxicity, and achieves the effect of high selectivity and strong fluorescence detection of metal ions in seawater, especially trivalent iron ions. Moreover, the preparation process is environmentally friendly and non-toxic.
Patent Information
- Application Number
- CN202310682883.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2043-06-09
AI Technical Summary
Existing fluorescent sensor materials are prone to aggregation, have poor biocompatibility, and are toxic to the environment and organisms, which limits their application in seawater detection.
A complex formed by 2,2'-bipyridine and laminarin polysaccharide with trivalent terbium ions enhances fluorescence intensity through a ligand-metal charge transfer (LMCT) mechanism. The preparation process uses non-toxic solvents to form a core-shell structured fluorescent sensor material.
The prepared fluorescent sensor material has a stable structure, high selectivity and strong fluorescence intensity, and can quickly detect the concentration of metal ions in seawater, especially ferric ions. Moreover, the preparation process is environmentally friendly and non-toxic.
Smart Images

Figure CN117050747B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of fluorescent sensors, and particularly relates to a fluorescent sensor material for detecting metal ions in seawater and a preparation method and application thereof. BACKGROUND
[0002] Metals are important elements of the earth's crust, including aluminum, iron, calcium, sodium, potassium, magnesium, etc. With the increasing frequency of human activities, such as industrial waste discharge, coastal construction and dredging, etc., the concentration of metal ions in seawater is inevitably increased. Therefore, detecting the concentration of metal ions in seawater is crucial for the marine ecosystem.
[0003] The fluorescent detection method can realize the tracking detection of metal ions in seawater without destroying the biological activity and polluting the environment by means of fluorescent sensor technology, and plays an important role in the detection of metal ions. The existing fluorescent detection method uses a fluorescent sensor material composed of rare earth ions and ligands. An organic ligand is selected, the organic ligand is dissolved in an organic solvent, and then the organic ligand is self-assembled with rare earth ions. By means of "antenna effect", the energy transfer between the organic ligand and the rare earth ions is used to enhance the luminescence of the rare earth ions. Such fluorescent sensor material is easy to aggregate, has poor biocompatibility, and the organic solvent used in the preparation process usually has high toxicity, such as N,N-dimethylformamide and tetrahydrofuran, which is toxic to the environment and organisms, limiting the application of the fluorescent sensor material in seawater detection. SUMMARY
[0004] The purpose of the present application is to provide a fluorescent sensor material for detecting metal ions in seawater and a preparation method and application thereof, aiming to solve the problems of the existing fluorescent sensor material, such as easy aggregation, poor biocompatibility, and toxic to the environment and organisms, which cannot meet the demand of detecting metal ions in seawater.
[0005] In order to solve the above technical problems, the technical scheme of the present application is as follows:
[0006] In one aspect, the present application provides a fluorescent sensor material for detecting metal ions in seawater, wherein the fluorescent sensor material is a complex formed by simultaneously complexing 2,2'-dipyridyl ligand and laminarin ligand with trivalent terbium ions, and the structure of the fluorescent sensor material is shown as formula (I).
[0007]
[0008] Wherein, 0.01≤x≤1.
[0009] The fluorescent sensor material of the present application uses 2,2'-dipyridyl and laminarin as trivalent rare earth metal terbium ions (Tb 3+ ) ligand, 2,2'-bipyridine, laminarin and rare earth metal terbium ion organic complex; the electronic configuration of the rare earth metal terbium (Tb) is: [Kr]4d 10 4f 9 5s 2 5p 6 6s 2 , which is easy to lose 3 electrons (1 unpaired electron on the 4f orbital and two electrons on the 6s orbital), and is trivalent; the electronic configuration of Tb 3+ is [Kr]4d 10 4f 8 5s 2 5p 6 ; the electronic distribution of the O atom is: 1s 2 2s 2 2p 4 , and the electronic distribution of the N atom is: 1s 2 2s 2 2p 3 ; the laminarin structure contains a large number of hydroxyl groups, and the hydroxyl oxygen atom has a lone pair of electrons; the nitrogen atoms on the two pyridine rings in the 2,2'-bipyridine structure have a lone pair of electrons; the 6s, 5d, and 6p of Tb 3+ have empty orbitals, which can accept the lone pair of electrons on the hydroxyl oxygen and pyridine nitrogen, forming a coordination bond; the oxygen atoms in the laminarin have coordination with Tb 3+ , and the nitrogen atoms in the 2,2'-bipyridine have coordination with Tb 3+ , generating new chemical bonds-Tb-O and Tb-N; this fluorescent sensor material is stable in structure, realizes luminescence through the ligand-metal charge transfer (LMCT) mechanism, sensitizes the luminescence of Tb 3+ , enhances the luminescence intensity of Tb 3+ , and has strong fluorescence intensity; this fluorescent sensor material combines the good luminescence characteristics of the rare earth metal terbium ion and the non-toxicity and biocompatibility of laminarin, has good dispersibility, and has no toxic effect on the environment and organisms, plus the enhancement effect of 2,2'-bipyridine on the luminescence fluorescence intensity of the rare earth metal terbium ion, this fluorescent sensor material has high selectivity for metal ions in seawater, and is widely used for the detection of metal ions in seawater.
[0010] As a preferred embodiment, the mass percentage of each component in the fluorescent sensor material is: 19.4-49.7% of trivalent terbium ions, 19.0-48.8% of 2,2'-bipyridine, and 1.5-61.6% of laminarin. In the fluorescent sensor material of the present application, 2,2'-bipyridine, laminarin and rare earth metal terbium ions are organically combined. 2,2'-bipyridine has the effect of enhancing the fluorescence intensity of the luminescence of trivalent terbium ions, and 2,2'-bipyridine is coordinated with trivalent terbium ions by nitrogen atoms. Laminarin is an organic macromolecule. Laminarin has a long molecular chain, a stable molecular structure without double bonds, a complex molecular structure and large steric hindrance. Laminarin is coordinated with Tb 3+ by oxygen atoms.
[0011] As a preferred embodiment, the morphology of the fluorescent sensor material is circular. In the fluorescent sensor material of the present application, laminarin is a non-toxic, water-soluble, natural biological extracted polysaccharide, which is coordinated with Tb 3+ to form a coordination effect, and gives Tb 3+ luminescent material new characteristics of non-toxicity, water-solubility and environmental friendliness. As a ligand, Tb 3+ is sensitized to luminescence, greatly enhancing the green fluorescence of Tb 3+ , which is emitted through the ligand-metal charge transfer (LMCT) mechanism.
[0012] As a preferred embodiment, the structure of the fluorescent sensor material is a core-shell structure, and the fluorescent sensor material has trivalent terbium ions and 2,2'-bipyridine as the core and laminarin as the shell. In the fluorescent sensor material of the present application, laminarin has a macromolecular structure, is easy to form a film, can wrap rare earth metal terbium ions and 2,2'-bipyridine, and form a fluorescent sensor material with a core-shell structure. The general formula of the molecular structure of the fluorescent sensor material of the present application is: Tb(2,2'-Bipyridine)(Laminarin)x, wherein Tb is trivalent terbium ions, 2,2'-Bipyridine is 2,2'-bipyridine, and Laminarin is laminarin.
[0013] In another aspect, the application provides a method for preparing a fluorescent sensor material for detecting metal ions in seawater, comprising the following steps: 1) taking a soluble inorganic salt of trivalent terbium, adding it into anhydrous ethanol, stirring, dissolving, and preparing a trivalent terbium salt ethanol solution with a molar concentration of 0.01-0.10 mol / L; 2) taking 2,2'-bipyridine, adding it into anhydrous ethanol, stirring, dissolving, and preparing a 2,2'-bipyridine ethanol solution with a molar concentration of 0.01-0.10 mol / L; 3) taking laminarin, adding it into water, stirring, dissolving, and preparing a laminarin aqueous solution with a molar concentration of 0.0001-0.1000 mol / L; 4) mixing the trivalent terbium salt ethanol solution obtained in step 1) with the 2,2'-bipyridine ethanol solution obtained in step 2), the molar ratio of trivalent terbium ions in the trivalent terbium salt ethanol solution to 2,2'-bipyridine in the 2,2'-bipyridine ethanol solution being 1:1-3, stirring at room temperature for 1-2 h, and obtaining a ligand mixture; and 5) adding the laminarin aqueous solution obtained in step 3) into the ligand mixture obtained in step 4), the molar ratio of laminarin in the laminarin aqueous solution to trivalent terbium ions in the trivalent terbium salt ethanol solution being 0.01-1:1, stirring at room temperature for 2-3 h, and obtaining the fluorescent sensor material.
[0014] The method for preparing the fluorescent sensor material for detecting metal ions in seawater of the application uses anhydrous ethanol and water as solvents, which are non-toxic and harmless to the environment and organisms; in addition, laminarin is also a non-toxic substance, has good water solubility, and is obtained by extraction from natural organisms; therefore, the method for preparing the fluorescent sensor material for detecting metal ions in seawater of the application is simple to operate, does not use organic solvents with toxicity, and the non-toxic laminarin wraps the trivalent terbium ions and 2,2'-bipyridine, so that the preparation process is green and environmentally friendly, the conditions are mild, and industrialization is easy to realize.
[0015] As a preferred embodiment, in step 1), the soluble inorganic salt of trivalent terbium is terbium chloride or terbium nitrate. The terbium chloride or terbium nitrate of the application can be dissolved not only in water but also in anhydrous ethanol, has good solubility, and can release trivalent rare earth metal terbium ions. In the application, preferably, 0.01≤x≤0.1, at this time, the molar ratio of laminarin in the laminarin aqueous solution to trivalent terbium ions in the trivalent terbium salt ethanol solution in the preparation process of the fluorescent sensor material is 0.01-0.1:1.
[0016] As a preferred embodiment, in step 4), the stirring speed during stirring is 600-1200 r / min. The application accelerates the mixing of the terbium salt ethanol solution and the 2,2'-bipyridine ethanol solution under the action of stirring, makes them fully dispersed, and improves the uniformity of mixing.
[0017] As a preferred embodiment, in step 5), the stirring speed is 600-1200 r / min. The present invention accelerates the mixing of the ligand mixture and the laminarin aqueous solution under the action of stirring, allowing the laminarin aqueous solution to be fully dispersed in the ligand mixture, enhancing the coordination of the trivalent rare earth metal terbium ion with laminarin and 2,2'-bipyridine, and improving the stability and dispersibility of the complex.
[0018] In another aspect, the present invention provides an application of a fluorescent sensor material for detecting metal ions in seawater, wherein the fluorescent sensor material is used to detect metal ions in seawater. The fluorescent sensor material of the present invention has a strongest emission peak at 547 nm under 350 nm excitation, which belongs to Tb 3+ of 5 D4- 7 F5 transition can be used to detect metal ions in seawater; this fluorescent sensor material has Tb 3+ The green fluorescence of the sample decreases until it is quenched after adding the metal ions to be tested, and the concentration of metal ions in seawater can be quantitatively detected.
[0019] As a preferred embodiment, the fluorescent sensor material is used to detect trivalent iron ions in seawater. When the fluorescent sensor material of the present invention detects metal ions in seawater, the metal ions coordinate with oxygen atoms on laminarin and nitrogen atoms in 2,2'-bipyridine, reducing energy transfer from laminarin and 2,2'-bipyridine ligands to trivalent rare earth metal terbium ions. As a result, the metal ions can reduce the fluorescence intensity of the fluorescent sensor material. As the metal ion concentration increases, the fluorescence intensity gradually decreases until it is quenched. Therefore, the fluorescent sensor material of the present invention can quickly detect the concentration of metal ions in seawater, and in particular, selectively identify trivalent iron ions.
[0020] Compared with the prior art, the present invention has the following advantages: the fluorescent sensor material of the present invention uses 2,2'-bipyridine and laminarin as trivalent rare earth metal terbium ions (Tb 3+ ) ligand, 2,2'-bipyridine, laminarin and rare earth metal terbium ion organic coordination, the oxygen atoms in laminarin and Tb 3+ A coordination effect occurs, and the nitrogen atom in 2,2'-bipyridine and Tb 3+ A coordination effect occurs, generating new chemical bonds - Tb-O and Tb-N; this fluorescent sensor material has a stable structure and emits light through the ligand-metal charge transfer (LMCT) mechanism, sensitizing Tb 3+ The luminescence of Tb 3+The luminescent intensity of the terbium ion is enhanced by 2,2'-bipyridine, and the fluorescent sensor material has high selectivity for metal ions in seawater, is widely used for detection of metal ions in seawater, can rapidly detect the concentration of metal ions in seawater, and especially selectively recognizes ferric ions. The preparation method of the fluorescent sensor material for detecting metal ions in seawater is simple, does not use toxic organic solvents, and the nontoxic ligand laminarin wraps the terbium ion and 2,2'-bipyridine, so that the preparation process is green and environmentally friendly, the conditions are mild, and industrialization is easy to realize. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 A transmission electron microscope image of the fluorescent sensor material obtained in Example One of the present application;
[0022] Figure 2 A transmission electron microscope image of the fluorescent sensor material obtained in Example Two of the present application;
[0023] Figure 3 A transmission electron microscope image of the fluorescent sensor material obtained in Example Three of the present application;
[0024] Figure 4 A fluorescent emission spectrum diagram of the fluorescent sensor material obtained in Example One of the present application;
[0025] Figure 5 A fluorescent emission spectrum diagram of the fluorescent sensor material obtained in Example Two of the present application;
[0026] Figure 6 A fluorescent emission spectrum diagram of the fluorescent sensor material obtained in Example Three of the present application;
[0027] Figure 7 A fluorescent response diagram of the fluorescent sensor material obtained in Example Three of the present application to different metal ions;
[0028] Figure 8 A fluorescent emission spectrum diagram of the fluorescent sensor material obtained in Example Three of the present application to different concentrations of Fe 3+
[0029] Figure 9 A schematic diagram of the luminescence mechanism and energy transfer process of the terbium ion sensitized by laminarin and 2,2'-bipyridine in the present application. DETAILED DESCRIPTION
[0030] The technical solutions of the present application will be clearly and completely described below in combination with specific embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative efforts belong to the protection scope of the present application.
[0031] The present application provides a fluorescent sensor material for detecting metal ions in seawater, wherein the fluorescent sensor material is a complex formed by simultaneously complexing trivalent terbium ions with 2,2'-bipyridine ligands and laminarin ligands, and a structural formula of the fluorescent sensor material is shown as formula (I).
[0032]
[0033] wherein 0.01<=x<=1.
[0034] Preferably, the mass percentage of each component in the fluorescent sensor material is as follows: 19.4-49.7% of trivalent terbium ions, 19.0-48.8% of 2,2'-bipyridine, and 1.5-61.6% of laminarin.
[0035] Preferably, the morphology of the fluorescent sensor material is circular.
[0036] Further, the structure of the fluorescent sensor material is a core-shell structure, wherein the fluorescent sensor material takes trivalent terbium ions and 2,2'-bipyridine as the core and takes laminarin as the shell.
[0037] The present application provides a preparation method of a fluorescent sensor material for detecting metal ions in seawater, and the method comprises the following steps:
[0038] 1) A soluble inorganic salt of trivalent terbium is taken, added into anhydrous ethanol, stirred, dissolved, and a trivalent terbium salt ethanol solution with a molar concentration of 0.01-0.10 mol / L is prepared;
[0039] 2) 2,2'-bipyridine is taken, added into anhydrous ethanol, stirred, dissolved, and a 2,2'-bipyridine ethanol solution with a molar concentration of 0.01-0.10 mol / L is prepared;
[0040] 3) Laminarin is taken, added into water, stirred, dissolved, and a laminarin aqueous solution with a molar concentration of 0.0001-0.1000 mol / L is prepared;
[0041] 4) The trivalent terbium salt ethanol solution obtained in step 1) and the 2,2'-bipyridine ethanol solution obtained in step 2) are mixed, the molar ratio of trivalent terbium ions in the trivalent terbium salt ethanol solution to 2,2'-bipyridine in the 2,2'-bipyridine ethanol solution is 1:1-3, and the mixture is stirred at room temperature for 1-2 h to obtain a ligand mixture.
[0042] 5) adding the laminarin aqueous solution obtained in step 3) into the ligand mixture obtained in step 4), the molar ratio of laminarin in the laminarin aqueous solution to the trivalent terbium ion in the trivalent terbium salt ethanol solution being 0.01-1:1, stirring at room temperature for 2-3 h to obtain the fluorescent sensor material.
[0043] Preferably, in the step 1), the soluble inorganic salt of trivalent terbium is terbium chloride or terbium nitrate.
[0044] Preferably, in the step 4), the stirring speed is 600-1200 r / min.
[0045] Preferably, in the step 5), the stirring speed is 600-1200 r / min.
[0046] The application of the fluorescent sensor material for detecting metal ions in seawater.
[0047] Preferably, the fluorescent sensor material is used for detecting trivalent iron ions in seawater.
[0048] Example I
[0049] The preparation method of the fluorescent sensor material for detecting metal ions in seawater comprises the following steps:
[0050] 1) taking 0.373 g of terbium trichloride hexahydrate, adding into 20 mL of anhydrous ethanol, stirring, dissolving, and using anhydrous ethanol to make up to 100 mL in a volumetric flask to prepare a trivalent terbium salt ethanol solution with a molar concentration of 0.01 mol / L;
[0051] 2) taking 0.156 g of 2,2'-dipyridyl, adding into 20 mL of anhydrous ethanol, stirring, dissolving, and using anhydrous ethanol to make up to 100 mL in a volumetric flask to prepare a 2,2'-dipyridyl ethanol solution with a molar concentration of 0.01 mol / L;
[0052] 3) taking 0.0050 g of laminarin, adding into 20 mL of water, stirring, dissolving, and using water to make up to 100 mL in a volumetric flask to prepare a laminarin aqueous solution with a molar concentration of 0.0001 mol / L;
[0053] 4) taking 10 mL of the trivalent terbium salt ethanol solution obtained in step 1) and 10 mL of the 2,2'-dipyridyl ethanol solution obtained in step 2), mixing, stirring at room temperature for 1 h to obtain a ligand mixture;
[0054] 5) Take 10 mL of the laminarin aqueous solution obtained in step 3) and add to the ligand mixture obtained in step 4), stir at room temperature for 2 h to obtain the fluorescent sensor material.
[0055] Example 2
[0056] The application discloses a preparation method of a fluorescent sensor material for detecting metal ions in seawater.
[0057] 1) Take 0.923 g of terbium nitrate hexahydrate, add to 20 mL of anhydrous ethanol, stir, dissolve, and use anhydrous ethanol to make up to 100 mL in a volumetric flask to prepare a terbium salt ethanol solution with a molar concentration of 0.02 mol / L;
[0058] 2) Take 0.312 g of 2,2'-bipyridine, add to 20 mL of anhydrous ethanol, stir, dissolve, and use anhydrous ethanol to make up to 100 mL in a volumetric flask to prepare a 2,2'-bipyridine ethanol solution with a molar concentration of 0.02 mol / L;
[0059] 3) Take 5.0000 g of laminarin, add to 20 mL of water, stir, dissolve, and use water to make up to 100 mL in a volumetric flask to prepare a laminarin aqueous solution with a molar concentration of 0.1000 mol / L;
[0060] 4) Take 10 mL of the terbium salt ethanol solution obtained in step 1) and 10 mL of the 2,2'-bipyridine ethanol solution obtained in step 2), mix, stir at room temperature for 2 h to obtain a ligand mixture;
[0061] 5) Take 10 mL of the laminarin aqueous solution obtained in step 3) and add to the ligand mixture obtained in step 4), stir at room temperature for 3 h to obtain the fluorescent sensor material.
[0062] Example 3
[0063] The application discloses a preparation method of a fluorescent sensor material for detecting metal ions in seawater.
[0064] 1) Take 1.865 g of terbium trichloride hexahydrate, add to 20 mL of anhydrous ethanol, stir, dissolve, and use anhydrous ethanol to make up to 100 mL in a volumetric flask to prepare a terbium salt ethanol solution with a molar concentration of 0.05 mol / L;
[0065] 2) Take 0.78 g of 2,2'-bipyridine, add to 20 mL of anhydrous ethanol, stir, dissolve, and use anhydrous ethanol to make up to 100 mL in a volumetric flask to prepare a 2,2'-bipyridine ethanol solution with a molar concentration of 0.05 mol / L;
[0066] 3) take laminarin polysaccharide 0.050 g, add 20 mL of water, stir, dissolve, and use water to make up to 100 mL in a volumetric flask, to make a 0.001 mol / L aqueous solution of laminarin polysaccharide;
[0067] 4) take 10 mL of the terbium salt ethanol solution obtained in step 1) and 20 mL of the 2,2'-bipyridine ethanol solution obtained in step 2), mix, stir at room temperature for 1.5 h, to obtain a ligand mixture;
[0068] 5) take 10 mL of the laminarin polysaccharide aqueous solution obtained in step 3), add to the ligand mixture obtained in step 4), stir at room temperature for 2.5 h, to obtain a fluorescent sensor material.
[0069] Experiment 1
[0070] Take 200-mesh carbon film copper mesh with tweezers, fish the three fluorescent sensor materials obtained in Example One to Example Three of the application, dry under an infrared lamp, and place on a JEM-1200CXII type transmission electron microscope produced by Japan Electronics Corporation for observation. Figure 1 , attached Figure 2 and attached Figure 3 It can be seen that the fluorescent sensor material obtained by the method of the application has a circular structure, which is a core-shell structure composed of a core and a shell. The core is terbium ions and 2,2'-bipyridine, and the shell is laminarin. Since laminarin also forms a coordination with terbium ions through oxygen atoms, and laminarin is easy to form a film, the core in this core-shell structure is not completely located at the center point of the circular structure, but is offset and wrapped by the shell formed by laminarin.
[0071] Experiment 2
[0072] Take another 3 mL of the three fluorescent sensor materials obtained in Example One to Example Three of the application, respectively, and add to 10 mm four-way quartz cuvettes, and measure the fluorescence spectrum on a F-4500 type spectrometer produced by Hitachi under 350 nm excitation. From attached Figure 4 , attached Figure 5 and attached Figure 6 It can be seen that the three fluorescent sensor materials obtained by the application all show very strong fluorescence intensity peaks at 547 nm under 350 nm excitation when the fluorescence performance is tested. This shows that the fluorescent sensor material obtained by the application has good fluorescence emission performance.
[0073] Experiment 3
[0074] Take the fluorescent sensor material obtained in Example Three of the application as an example to perform a fluorescence response selectivity experiment of different metal ions in seawater. Take standard seawater and prepare Ca2+ Mg 2+ K + Na + Zn 2+ Al 3+ Mn 2+ Cr 3+ Ni 2+ Cu 2+ Co 2+ and Fe 3+ Molar concentration of 0.1 mol / L seawater solution, take 12 of the obtained fluorescent sensor material of example three each 4 mL, on the F-4500 type spectrum measuring instrument of Hitachi company, under the same parameter, determine its fluorescence spectrum, under the excitation of 350 nm, the fluorescence intensity obtained at 547 nm is recorded as I0. Then, respectively add 10 μL of the above seawater solution, get test solution, on the F-4500 type spectrum measuring instrument of Hitachi company, under the same parameter, determine its fluorescence spectrum, under the excitation of 350 nm, the fluorescence intensity obtained at 547 nm is recorded as I, get the ratio of the two, that is: I / I0.
[0075] By attaching Figure 7 It can be seen that the fluorescent sensor material obtained by the present application has the fluorescence performance test with the test solution containing metal ions Ca 2+ Mg 2+ K + Na + Zn 2+ Al 3+ Mn 2+ Cr 3+ Ni 2+ Cu 2+ Co 2+ and Fe 3+ The fluorescence intensity of the test solution containing ferric ion is the most obvious, and the ratio of I / I0 is the smallest; the fluorescence intensity of the test solution containing other metal ions is basically unchanged or slightly reduced. Since the fluorescent sensor material obtained by the present application has very strong fluorescence intensity, after adding the seawater solution containing ferric ion, the fluorescence intensity is quenched, and Fe 3+ Therefore, the fluorescent sensor material of the present application can selectively recognize Fe 3+ .
[0076] Experiment 4
[0077] Take the fluorescent sensor material obtained in example three of the present application as an example to carry out the fluorescence titration experiment of ferric ion. Take the fluorescent sensor material obtained in example three of the present application 9, each 4 mL, and add the seawater solution of ferric chloride with a molar concentration of 0.1 mol / L, and respectively configure into Fe 3+The molar concentration of the solution is 0 μmol / L, 25 μmol / L, 50 μmol / L, 75 μmol / L, 100 μmol / L, 150 μmol / L, 200 μmol / L, 250 μmol / L and 300 μmol / L respectively, and the test liquid is obtained, and the fluorescence emission spectrum is measured on the F-4500 type spectrum measuring instrument produced by Hitachi company under the excitation of 350 nm. The fluorescence intensity obtained at 547 nm under the excitation of 350 nm is recorded as I, and the ratio of I / I0 is obtained. 3+ The molar concentration of the solution is 0 μmol / L, 25 μmol / L, 50 μmol / L, 75 μmol / L, 100 μmol / L, 150 μmol / L, 200 μmol / L, 250 μmol / L and 300 μmol / L respectively, and the test liquid is obtained, and the fluorescence emission spectrum is measured on the F-4500 type spectrum measuring instrument produced by Hitachi company under the excitation of 350 nm. The fluorescence intensity obtained at 547 nm under the excitation of 350 nm is recorded as I, and the ratio of I / I0 is obtained.
[0078] The fluorescence intensity obtained at 547 nm under the excitation of 350 nm is recorded as I, and the ratio of I / I0 is obtained. Figure 8 It can be seen that, with the increase of the molar concentration of Fe 3+ , the fluorescence intensity gradually weakens; when the molar concentration of Fe 3+ is 300 μmol / L, the fluorescence is quenched. Therefore, the fluorescence sensor material obtained by the application can be used as a fluorescence response reagent for the identification of Fe 3+ in seawater. During the experiment, after the seawater solution of Fe 3+ is added into the fluorescence sensor material obtained by the application, the mixture is shaken for 1-2 seconds, and then the fluorescence test is immediately carried out, and the fluorescence response occurs, and the fluorescence is weakened or quenched. Therefore, the response speed of the fluorescence sensor material obtained by the application to Fe 3+ is fast.
[0079] The fluorescence intensity obtained at 547 nm under the excitation of 350 nm is recorded as I, and the ratio of I / I0 is obtained. Figure 9 It can be seen that, under the excitation of 350 nm, the laminarin and 2,2'-dipyridyl act as ligands for sensitizing the luminescence of the trivalent terbium ion (Tb 3+ ), and the electrons are transferred from the ground state to the excited state. 3+ Part of the electrons falls back to the ground state, and part of the electrons migrates to the transition state (T1) to excite the electrons of Tb 3+ The excited electrons of Tb 3+ fall back to the ground state to produce fluorescence at 547 nm.
[0080] Therefore, compared with the prior art, the beneficial effects of the application are as follows: the fluorescence sensor material of the application uses 2,2'-dipyridyl and laminarin as ligands for the trivalent rare earth metal terbium ion (Tb 3+ ), and the 2,2'-dipyridyl, laminarin and rare earth metal terbium ion are organically combined, and the oxygen atoms in the laminarin excite the Tb 3+Coordination occurs, nitrogen atoms in 2,2'-bipyridine and Tb 3+ Coordination occurs, new chemical bonds are generated, namely Tb-O and Tb-N; the fluorescent sensor material is stable in structure, realizes luminescence through a ligand-metal charge transfer (LMCT) mechanism, sensitizes the luminescence of Tb 3+ , enhances the luminescence intensity of Tb 3+ , and has strong fluorescence intensity; the fluorescent sensor material combines the good luminescence characteristics of rare earth metal terbium ions and the non-toxicity and biocompatibility of laminarin, has good dispersibility, and has no toxic effects on the environment and organisms; in addition, 2,2'-bipyridine enhances the luminescence fluorescence intensity of rare earth metal terbium ions; the fluorescent sensor material has high selectivity for metal ions in seawater, is widely used for detecting metal ions in seawater, can rapidly detect the concentration of metal ions in seawater, and especially selectively recognizes trivalent iron ions. The preparation method of the fluorescent sensor material for detecting metal ions in seawater is simple to operate, does not use toxic organic solvents, and has no toxic ligand laminarin wrapped around terbium ions and 2,2'-bipyridine; the preparation process is green and environmentally friendly, the conditions are mild, and industrialization is easy to realize.
[0081] The above merely describes preferred embodiments of the present application and is not intended to limit the present application, and any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A fluorescent sensor material for detecting metal ions in seawater, characterized by: The fluorescent sensor material is a complex formed by the simultaneous complexation of 2,2'-bipyridine ligands and laminarin ligands with trivalent terbium ions. The mass percentages of the components in the fluorescent sensor material are: 19.4-49.7% trivalent terbium ions, 19.0-48.8% 2,2'-bipyridine, and 1.5-61.6% laminarin. The structural formula of the fluorescent sensor material is shown in formula (I): Formula (I); Among them, 0.01≤x≤1.
2. The fluorescent sensor material for detecting metal ions in seawater according to claim 1, characterized in that: The shape of the fluorescent sensor material is circular.
3. The fluorescent sensor material for detecting metal ions in seawater according to claim 2, characterized in that: The structure of the fluorescent sensor material is a core-shell structure, wherein the fluorescent sensor material has trivalent terbium ions and 2,2'-bipyridine as a core and laminarin as a shell.
4. A method for preparing a fluorescent sensor material for detecting metal ions in seawater according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) taking a soluble inorganic salt of trivalent terbium, adding it to anhydrous ethanol, stirring and dissolving it to prepare a trivalent terbium salt ethanol solution with a molar concentration of 0.01-0.10 mol / L; 2) Take 2,2'-bipyridine, add it to anhydrous ethanol, stir and dissolve it to prepare a 2,2'-bipyridine ethanol solution with a molar concentration of 0.01-0.10 mol / L; 3) Add laminarin to water, stir, and dissolve to prepare a laminarin aqueous solution with a molar concentration of 0.0001-0.1000 mol / L; 4) mixing the trivalent terbium salt ethanol solution obtained in step 1) with the 2,2'-bipyridine ethanol solution obtained in step 2), wherein the molar ratio of trivalent terbium ions in the trivalent terbium salt ethanol solution to 2,2'-bipyridine in the 2,2'-bipyridine ethanol solution is 1:1-3, and stirring at room temperature for 1-2 hours to obtain a ligand mixture; 5) adding the laminarin aqueous solution obtained in step 3) to the ligand mixture obtained in step 4), wherein the molar ratio of laminarin in the laminarin aqueous solution to trivalent terbium ions in the trivalent terbium salt ethanol solution is 0.01-1:1, and stirring at room temperature for 2-3 hours to obtain a fluorescent sensor material.
5. The method for preparing a fluorescent sensor material for detecting metal ions in seawater according to claim 4, characterized in that: In the step 1), the soluble inorganic salt of trivalent terbium is terbium chloride or terbium nitrate.
6. The method for preparing a fluorescent sensor material for detecting metal ions in seawater according to claim 4, characterized in that: In the step 4), the stirring speed is 600-1200 r / min.
7. The method for preparing a fluorescent sensor material for detecting metal ions in seawater according to claim 4, characterized in that: In step 5), the stirring speed is 600-1200 r / min.
8. Use of the fluorescent sensor material for detecting metal ions in seawater according to any one of claims 1 to 3, characterized in that: The fluorescent sensor material is used for detecting trivalent iron ions in seawater.